Population genomics of a natural Cannabis sativa L. collection from Iran identifies novel genetic loci for flowering time, morphology, sex and chemotyping - Mahboubeh Mostafaei Dehnavi; Annabelle Damerum; Sadegh Taheri; Ali Ebadi; Shadab Panahi; George Hodgin; Brian Brandley; Seyed Alireza Salami; Gail Taylor (BMC Plant Biology)
Abstract Background Future breeding and selection of Cannabis sativa L. for both drug production and industrial purposes require a source of germplasm with wide genetic variation, such as that found in wild relatives and progenitors of highly cultivated plants. Limited directional selection and breeding have occurred in this crop, especially informed by molecular markers. Results This study investigated the population genomics of a natural cannabis collection comprising male and female individuals from various climatic zones in Iran. Using Genotyping-By-Sequencing (GBS), we sequenced 228 individuals from 35 populations. The data obtained enabled an association analysis, linking genotypes with key phenotypes such as inflorescence characteristics, flowering time, plant morphology, tetrahydrocannabinol (THC) and cannabidiol (CBD) content, and sex. We detected approximately 23,266 significant high-quality Single Nucleotide Polymorphisms (SNPs), establishing associations between markers and traits. The population structure analysis revealed that Iranian cannabis plants fall into five distinct groups. Additionally, a comparison with global data suggested that the Iranian populations is distinctive and generally closer to marijuana than to hemp, with some populations showing a closer affinity to hemp. The GWAS identified novel genetic loci associated with sex, yield, and chemotype traits in cannabis, which had not been previously reported. Conclusion The study's findings highlight the distinct genetic structure of Iranian Cannabis populations. The identification of novel genetic loci associated with important traits suggests potential targets for future breeding programs. This research underscores the value of the Iranian cannabis germplasm as a resource for breeding and selection efforts aimed at improving Cannabis for various uses.